Nuclear power and energy security in Asia - Basrur, Rajesh M.; Koh, Swee Lean Collin, 1982- (Milton Park, Abingdon, Oxon : Routledge, 2013)
'The rising demand for energy, the higher costs of oil and gas, and the association of fossil fuels with adverse climate change have all brought a renewed interest in nuclear energy. Nuclear power, however, is itself controversial, because of its costs, its environmental effects and the security risks it poses. This book discusses these critical issues surrounding nuclear power in relation to Asia. It discusses also the politics of nuclear power and the activities of civil society organisations concerned about nuclear issues. Throughout the book the perspectives are included of both proponents and opponents of nuclear power on the key controversial issues.'--Publisher's description.
Nuclear energy and energy security in Asia : through the human security lens / Rajesh Basrur, Koh Swee Lean and Kalyan M. Kemburi -- Is the rapid growth of reliance on nuclear energy an economically viable option? / Hooman Peimani -- The economics of nuclear energy / Mark Diesendorf -- Nuclear power and environmental impact : risk vs. perception / T.S. Gopi Rethinaraj -- Critical environmental questions : nuclear energy and human security in Asia / Simon S.C. Tay and Phir Paungmalit -- Nuclear energy and security risks / Jor-Shan Choi -- Nuclear power and proliferation : the risks of the nuclear'renaissance' / Miles A. Pomper and Cole J. Harvey -- Civil society organisations and the politics of nuclear energyin Southeast Asia : exploring processes of engagement / Mely Caballero-Anthony, Lina Alexandra and Kevin D.G. Punzalan -- Post-Fukushima : whither nuclear energy? / Rajesh Basrur, Koh Swee Lean Collin and Chang Youngho.
Includes bibliographical references and index.
Keywords: Nuclear industry -- Asia; Energy security -- Asia